If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-43=3x-10
We move all terms to the left:
4x-43-(3x-10)=0
We get rid of parentheses
4x-3x+10-43=0
We add all the numbers together, and all the variables
x-33=0
We move all terms containing x to the left, all other terms to the right
x=33
| 9+4x=-5+2x | | 1+3x=+3 | | 6y-12=3y+33 | | 9b+7+7b=-3b+12 | | 14−2h=–4 | | 2x+1+x+16+2x+31=180 | | 15x+8=128-3x | | 32(5+4m)=2+1m | | x6=412 | | 43-8=35-x | | 8x-7=2x+19 | | 7n−18=66 | | 56-5x=11 | | (3-z)(3z+1)=0 | | -9x-12=-66 | | (12x-36)=8x+12 | | -10x-8=10x-12 | | (12x-36)=(8x+12) | | 1/4y+4/5=1/3 | | x−135=67 | | x−135=67 | | -4(7x-2)+2=-9(x-3)-11 | | 10b-22=67 | | X+20+x-1=180 | | 3/x*4/7=12/56 | | 3/x*4/7=12/56 | | 5^(2n)=125 | | 4.98=x−7.03 | | 10.87=6.34+x | | 10.87=6.34+x. | | (8x+17)=(115) | | (x)=|2x+9| |